2022
DOI: 10.1186/s40359-021-00694-4
|View full text |Cite
|
Sign up to set email alerts
|

Home practice in mindfulness-based interventions for psychosis groups: a systematic review and qualitative study

Abstract: Background Regular home practice is considered a core component of mindfulness groups and may be associated with better treatment outcomes. This study aimed to (1) review the existing evidence on how much home practice people do in mindfulness-based interventions for psychosis groups, and (2) explore participants’ experiences of the barriers and facilitators to completing home practice in a mindfulness for psychosis group using a qualitative study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“… 45 High levels of digital literacy in developed countries indicate that their people are better able to access and use mental health technology, strengthening the adoption of digital mindfulness. 46 This adoption is also related to the unique cultural, social and economic context in each developed country. Governments and health institutions in developed countries need to consider these dynamics in designing effective strategies to promote mental health through digital solutions, while ensuring inclusivity and accessibility for all levels of society.…”
Section: Discussionmentioning
confidence: 99%
“… 45 High levels of digital literacy in developed countries indicate that their people are better able to access and use mental health technology, strengthening the adoption of digital mindfulness. 46 This adoption is also related to the unique cultural, social and economic context in each developed country. Governments and health institutions in developed countries need to consider these dynamics in designing effective strategies to promote mental health through digital solutions, while ensuring inclusivity and accessibility for all levels of society.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque se pueden entregar ejercicios y prácticas en soporte digital para estimular la práctica en casa, esto debe plantearse como una opción no obligatoria, para que cada persona adapte con flexibilidad la práctica a su situación personal. Hay personas con psicosis que pueden beneficiarse significativamente de dar continuidad en casa a la práctica (Jacobsen et al, 2022), mientras que para otras puede significar un importante estresor, a lo que se une no contar con la presencia física del terapeuta guía que actúa como regulador dando seguridad y confianza. Una práctica que podría ser recomendable entre sesiones puede ser la meditación de tres minutos de Segal (Chadwick, 2009), por su brevedad y simplicidad.…”
Section: Adaptando Las Mbi a La Psicosisunclassified
“…The ethos when working with people with psychosis is that home practice is encouraged and supported, but is not a formal requirement or expectation (Chadwick., 2006). In a recent systematic review of home practice in mindfulness for psychosis interventions, 5/43 studies reported data on amount of home practice and none examined the association between home practice and clinical outcomes ( Jacobsen et al, 2022). Monitoring and evaluation of mindfulness practice between therapies and during any follow-up phase is a clear priority for future research.…”
Section: Is Home Practice Essential and Related To Clinical Outcomes?mentioning
confidence: 99%